Influence of the HIV GWG variant in the HIV infection progression in mono and HCV coinfected patients - Hebeler-Barbosa, Flavia [UNESP]; Massolini, Viviam Milanez; Watanabe, Thais [UNESP]; Silva, Giovanni Faria [UNESP]; Barbosa, Alexandre Naime [UNESP]; Simões, Rafael Plana [UNESP]; Ferrasi, Adriana Camargo [UNESP]; de Andrade Zanotto, Paolo Marinho; de Moura Campos Pardini, Maria Inês [UNESP]; Grotto, Rejane Maria Tommasini [UNESP] (Wolters Kluwer, 2019)
The HIV subtype B is the most frequent in Brazil. The HIV subtype B' codes the amino acids glicine-tryptophan-glicine (GWG) instead of glicine-proline-glicine on the tip of gp120 V3 loop. This variant was associated to a slower HIV progression in mono-infected patients; however, there is no information in coinfected patients. This study evaluated the infection progression of HIV variant B' on the hepatitis C virus presence. RNA isolated from plasma of the 601 infected patients were used to human immunodeficiency virus (HIV) subtyping and to classify the virus according their syncytium-inducing ability. The HIV infection progression was evaluated by clinical and laboratorial data. The results showed a significant association between HIV B' variant and CD4 count and time of AIDS in HIV mono-infected patients. Notwithstanding the fact that we did not find a direct association between GWG variant and AIDS and in HIV coinfected patients no mitigating effect due to GWG presence was found. We did observe that the association between GWG variant and CD4 counts is lost in coinfected patients. This is first work showing influence of the HIV GWG variant in coinfected patients. Nevertheless, the presence of the GWG variant can indicate a better prognostic in the mono-infected patients.